MENUJU PEMBANGUNAN BERWAWASAN KEPENDUDUKAN - Prijono Tjiptoherijanto (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2000)
The economic crisis in Indonesia, may be interpreted as effects of a strategy of economic development which has been unsuited to the Indonesian condition and potency. The strategy, so far has been oriented to the static development,top-down, and too formal. Therefore, it should be readapted to be more populist in order to promote the interest and needs of ordinary people. The bottom-upstrategy development with a basic populist concept has a primary goal to equalize the interest and wellfare of ordinary people, instead of emphasizing the levels of economic development. This strategy, is an effort to optimizing the distribution of its own natural resources, thus the development will correspond with the potency and specific issues of each region.